Mengenal Model Pendidikan High Scope Guna Memaksimalkan Potensi Anak: Understanding the High Scope Education Model to Maximize Children's Potential - Siti Nurma; Taopik Rahman (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
The High Scope learning model is an approach that emphasizes active learning in early childhood, where they are directly involved in exploration, interaction, and decision-making. This study aims to analyze the effectiveness of the High Scope model in supporting early childhood development in various aspects, including cognitive, social, emotional, and motoric. The method used is a literature study by reviewing various sources related to the implementation of this model. The results of the study indicate that High Scope, through the Plan-Do-Review strategy, can improve children's independence, critical thinking skills, and social abilities. In addition, long-term research reveals that this model has a positive impact on academic success, job opportunities, and individual well-being in the future. The main advantage of this approach is its flexibility, which allows adaptation to various cultures and local needs without changing its basic principles. The contribution of this study is to provide deeper insight into the implementation of the High Scope model and its relevance in the early childhood education system in Indonesia. By actively involving children, teachers, and parents in the learning process, this model is able to create a conducive learning environment for the development of children's skills and character from an early age.   ABSTRAK  Model pembelajaran High Scope merupakan pendekatan yang menekankan pembelajaran aktif pada anak usia dini, di mana mereka terlibat langsung dalam eksplorasi, interaksi, serta pengambilan keputusan. Penelitian ini bertujuan untuk menganalisis efektivitas model High Scope dalam mendukung perkembangan anak usia dini di berbagai aspek, termasuk kognitif, sosial, emosional, dan motorik. Metode yang digunakan adalah studi literatur dengan mengkaji berbagai sumber terkait implementasi model ini. Hasil penelitian menunjukkan bahwa High Scope, melalui strategi Plan-Do-Review, dapat meningkatkan kemandirian, keterampilan berpikir kritis, serta kemampuan sosial anak. Selain itu, penelitian jangka panjang mengungkapkan bahwa model ini berdampak positif terhadap keberhasilan akademik, peluang kerja, serta kesejahteraan individu di masa depan. Keunggulan utama dari pendekatan ini adalah fleksibilitasnya, yang memungkinkan adaptasi dengan berbagai budaya dan kebutuhan lokal tanpa mengubah prinsip dasarnya. Kontribusi penelitian ini adalah memberikan wawasan lebih dalam mengenai implementasi model High Scope serta relevansinya dalam sistem pendidikan anak usia dini di Indonesia. Dengan melibatkan anak, guru, dan orang tua secara aktif dalam proses pembelajaran, model ini mampu menciptakan lingkungan belajar yang kondusif untuk pengembangan keterampilan dan karakter anak sejak dini.